Compliance of Thai Tourists with the Smoke–Free Regulation as per the Notification of Ministry of Public Health (No.19) B.E. 2553: a Case Study Conducted with Hotels, Resorts or Bungalows, Tourist Attrac-tions and Public Transport Stations - Thaweesree, Thamarong; Pongpumma, Laksana (Journal of Health Science of Thailand, 2018)
Cigarette is harmful to smokers and people exposed to second-hand smoke. The purpose of this study was to explore behaviors of tourists in relation to their compliance with the smoke-free regulation as per the Notification of the Ministry of Public Health (No.19). It was conducted as a case study among Thai tourists staying in hotels, resorts or bungalows, tourist attractions, and public transport stations in Phetchaburi Province. The samples were 410 Thai tourists on their sightseeing trip in Phetchaburi Province during October – December 2017, who were selected by multi–stage sampling. The data were collected by using interview form and the group discussion with 18 public health personnel in public health offices about the implementation guidelines as well as problems and obstacles to work. The data were analyzed by percentage, chi–squared distribution, Pearson’ s correlation coefficient, while the qualitative data were analyzed by the content analysis . The findings of the study revealed that the majority of tourists, account-ing for 43.9% were moderately knowledgeable. Personal factors, knowledge on the smoke–free regulation in public places, and attitudes toward the smoke–free regulation in public places were negatively related to their behaviors in relation the smoke–free regulation in public places at a low level (r=-0.255, r=-0.368, p<0.05). The analysis on their opinions toward effects of smoking in such places indicated that the tourists who were exposed to cigarette odor or smoke would feel uncomfortable and sick after smelling cigarette smoke. The tourists expressed their opinions that public health personnel had not enforced the smoke-free regulation in public places in a serious and strict manner. Based on the group discussion, responsible personnel did not comply with the laws.